EVALUASI KETERSEDIAAN ARTIKEL JURNAL AKSES TERBUKA UNTUK CABANG ILMU MINYAK DAN GAS BUMI (EVALUATION OF THE AVAILABILITY OF OPEN ACCESS JOURNAL ARTICLE DISCIPLINES OF OILAND GAS) - Himawanto Himawanto (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2016)
To play an active role in increasing  the contribution  of knowledge  management  to society, a research on oil and gas needs access towell reputed scientific journal resources. However such resources are still difficult to find.  This condition has forced  researchers to find their own way in searching for information  they need. In order to support the research activities and reduce financial dependence, a disclosure on the availability of open access journals  has been done by evaluating a scientific journal reference namely the Scientific  Contribution Oil and Gas of 2010-2014. A descriptive study is used to find  out type of access, characteristics and data base. The results show that there are 492 articles used by researchers as their primary  reference. Most of these articles are accessible online and more than a half have open visibility. Morover; Scopus articles that are accessible for free  reach almost a half of the total population.  Open access journals  are likely to befound in database with .net domain and five years recentness. However, there are only few open access with DOI. The study also shows that articles written in Indonesian language are bigger in number than English articles. Open access journal articles are mostly made available by collaboration. Malaysia has shown its consistency in making the articles completely free.  Research  Gate as an alternative source plays  a potential  role in providing  Scopus reputable open access article. Moreover, researchers' awareness in making their own articles free for access through their affiliated database is believed to be one iffactors that will reduce the dependence on journal  subscriptions.